(untitled) (Al-Aasar, 2025)
Pakistan is a multi-ethnic country where translanguagingstrategies are often practiseddiscretely to support English language teaching.The study explores the translanguaging bilingual strategies used by the teachers in Pakistani educational institutions for young versus adult learners. The sample for this qualitative research was selected through the purposive sampling technique.English language teachers were interviewed until a saturation point was achieved. The study has focused on the teachers’ responses and observations of their classes thatwhen and how teachers apply several translanguaging strategies for their young and adult learners of the English language. Their responses were analyzed and compared through Jim Cummins’ CALP and BICS model exploring therelevant strategies for young and adult learners of Pakistan. The research would benefit researchers and educational legislatorstopromotestandardized translanguaging strategies designed for young and adult learners to improve their English languagecommunicative and cognitive abilities withinthe Pakistani educational setting.